Common fixed points of set-valued mappings - M. R. Singh; L. S. Singh; P. P. Murthy (International Journal of Mathematics and Mathematical Sciences)
The main purpose of this paper is to obtain a common fixed point for a pair of set-valued mappings of Greguš type condition. Our theorem extend Diviccaro et al. (1987), Guay et al. (1982), and Negoescu (1989).